LncRNA TP73-AS1 down-regulates miR-139-3p to promote retinoblastoma cell proliferation. Issue 5 (10th May 2019) - Xia, Zhaoxia; Yang, Xiaoxi; Wu, Shuduan; Feng, Zhizhen; Qu, Lei; Chen, Xianghua; Liu, Linyu; Ma, Yanling
Abstract : Our study aimed to investigate the role of long non-coding RNAs (lncRNA) TP73-AS1 in retinoblastoma (Rb). In the present study, we found that TP73-AS1 was up-regulated, while miR-139–3p was down-regulated in Rb. TP73-AS1 and miR-139-3p were inversely correlated in Rb tissues. In cells of Rb cell lines, overexpression of miR-139-3p failed to affect TP73-AS1, while TP73-AS1 overexpression caused the down-regulated miR-139-3p . TP73-AS1 overexpression caused promoted proliferation of Rb cells but showed no significant effects on cell migration and invasion. miR-139-3p overexpression played an opposite role and attenuated the effects of TP73-AS1 overexpression. Therefore, lncRNA TP73-AS1 may down-regulate miR-139-3p to promote Rb cell proliferation.